Reproductive Behavior of the Polyembryonic Parasitoid Copidosomopsis nacoleiae (Eady) at Different Ages - Huili Ouyang; Dongyu Chen; Peng Xiang; Xiaoyun Wang; Wen Lu; Xialin Zheng (Insects)
In the control of agricultural and forestry pests, excessive reliance on chemical pesticides has led to increasingly severe issues, such as toxic residues and heightened pest resistance. The effective use of biological control has become a major focus in pest management. Parasitoid wasps, as a critical natural enemy of pests, are widely distributed, diverse in species, and play an essential role in natural pest control. Copidosomopsis nacoleiae, a recently discovered polyembryonic endoparasitoid wasp, parasitizes Diaphania angustalis; yet, its biological characteristics remain insufficiently studied. The artificial rearing and population propagation of this wasp have not yet been achieved, and its reproductive behavior and rhythm are not fully understood. To better utilize natural enemy resources and maximize their pest control benefits, we conducted laboratory rearing, behavioral observation, and population surveys to investigate the morphological characteristics, life history, and behavioral patterns of C. nacoleiae. Under laboratory conditions, C. nacoleiae has a generational cycle of 48.71 ± 0.48 days, with an egg–larval period of 32.17 ± 0.20 days and a pupal period of 14.36 ± 0.27 days. Adult wasps require nutritional supplementation and have a maximum lifespan of 2.18 ± 0.09 days when fed 10% honey water. The pre-mating period for adults is 4.72 ± 0.24 h, with an average mating frequency of 5.17 ± 1.65 times per lifetime. Females have a pre-oviposition period of 2.80 ± 0.31 h and an oviposition period of 4.52 ± 0.12 h, laying between 2 and 95 eggs, with an average of 12.75 ± 9.99 eggs, totaling 107.55 ± 28.38 eggs over their lifespan. Offspring production increases with the body length of the host’s mature larvae. Through the successful establishment of a laboratory population of D. angustalis, the biological characteristics, reproductive behavior, and rhythms of C. nacoleiae were systematically examined in this study, and its occurrence dynamics in the field were investigated. These results provide a theoretical foundation for the large-scale propagation and application of C. nacoleiae to control D. angustalis populations effectively.